2013
DOI: 10.12660/rbfin.v11n4.2013.7224
|View full text |Cite
|
Sign up to set email alerts
|

Remuneração Executiva, Valor e Desempenho das Empresas Brasileiras Listadas

Abstract: The aim of this study is to identify the relationship between executive compensation, firm value and performance in Brazil. The literature provides mixed results but most studies show that firms with higher executive compensation tend to have greater value and performance in comparison with companies with lower compensation. We analyze a unique Brazilian database to test this hypothesis. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
5
0
6
Order By: Relevance
“…The result of this first hypothesis is consistent with the results of the studies conducted in Brazil by Silva and Chien (2013), Souza et al (2017), and Konraht et al (2018) who found no significant evidence between executive compensation and performance. They are also consistent with international studies such as those by Duffhues and Kabir (2008) and Barontini and Bozzi (2011), who found a negative relationship between executive compensation and company performance.…”
Section: Analysis and Discussion Of The Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The result of this first hypothesis is consistent with the results of the studies conducted in Brazil by Silva and Chien (2013), Souza et al (2017), and Konraht et al (2018) who found no significant evidence between executive compensation and performance. They are also consistent with international studies such as those by Duffhues and Kabir (2008) and Barontini and Bozzi (2011), who found a negative relationship between executive compensation and company performance.…”
Section: Analysis and Discussion Of The Resultssupporting
confidence: 89%
“…In Brazil, Silva and Chien (2013) found no significant evidence that companies that compensate their executives the most have better operating performance and higher value. Souza et al (2017) and Konraht et al (2018) also demonstrate the absence of statistical significance between executive compensation and market performance.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 93%
See 1 more Smart Citation
“…In the research by Silva and Chien (2013), the return on assets (ROA) and the sales variation did not present statistically significant relationships with the remuneration, contrary to the market value of the firm. Ferreira (2012) performed several tests to analyze relations between firm size and remuneration and did not find significant relationships.…”
Section: Literature Reviewmentioning
confidence: 80%
“…Nessa perspectiva, o desenho de um pacote de remuneração atrativo e compatível com a realidade do mercado, que apresente incentivos tanto de curto quanto de longo prazo e com metas claras de desempenho, é benéfico para a manutenção das relações entre acionistas e executivos (Silva & Chien, 2013). O que torna o fenômeno a ser observado ainda mais complexo é que os pacotes de compensação das empresas podem ser representados por inúmeros elementos, como salário-base, bônus anual, ações e opções de ações, seguros, benefícios de pensão e indenização (Georgen & Renneboog, 2011).…”
Section: Introductionunclassified